Synthesis and Bioactivities of Novel Galactoside Derivatives Containing 1,3,4-Thiadiazole Moiety - Shu, Yafei; Chen, Meihang; Lu, Daowang; Zhou, Zengyan; Yu, Jianhong; Hu, Xiaoling; Yang, Jiaqin; Li, Aiqin; Liu, Jianglong; Luo, Hairong (Frontiers in Chemistry, 2022)
A series of novel galactoside derivatives containing 1,3,4-thiadiazole moiety were synthesized and the tructure of them were verified by spectroscopy of NMR and HRMS, and antifungal and antibacterial activities of them were screened. The results showed that the newly synthesized compounds had good antifungal activities. Among of them, Ⅲ16, Ⅲ17, and Ⅲ19 exhibited satisfactory activities against Phytophthora infestans (P. infestans), with EC50 values of 5.87, 4.98, and 6.17 μg/mL, respectively, which were similar to that of Dimethomorph (5.52 μg/mL). Meanwhile, the title compounds also possessed certain antibacterial activities.